Implementasi Algoritme Grain-128 pada Wireless Sensor Network dengan Media Pengiriman Data nRF24L01 - Muhammad Khatib Barokah; Ari Kusyanti; Mochammad Ali Fauzi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
nRF24L01 is a data communication module commonly used on Wireless Sensor Network (WSN) devices. This communication module is often used because of its low power consumption and using little memory. The nRF24L01 module sends data by broadcasting it into an address. To receive data, the nRF24L01 module listen at the same address as well. However, this will create a vulnerability if the device is used to send data only to designated device. Therefore, a solution is needed to secure the data in the module such as implementing the Grain-128 algorithm. Grain-128 algorithm is an encryption algorithm that is designed to be implemented on hardware that requires limited resources. The Grain-128 algorithm is a variant of the Grain algorithm family. Grain-128 algorithm is a stream cipher where this algorithm requires 128 bit key input and 96 bit Initialization Vector (IV). That way, this study uses the Grain-128 algorithm to secure data communication with the nRF24L01 module in terms of confidentiality. Based on testing, the system takes 41363,25 micro seconds to generate keystream. The system also requires 12.02 and 12.26 micro seconds to encrypt and decrypt 8 bit data. The system is vulnerable to active attack but invulnerable to passive attack.